NCAPD3-mediated ferroptosis of 2,3,5,4’-Tetrahydroxystilbene-2-O-β-D-glucoside inhibits proliferation in T47D cells - Shen, Jianfen; Zhang, Shuo; Song, Yan; Yang, Leiming; Huang, Qi; Wang, Pengyu; Zhang, Youzhi (Frontiers in Pharmacology, 2025)
ObjectiveNon-SMC condensin II complex subunit D3 (NCAPD3) has recently been demonstrated as a crucial oncogenic factor, nevertheless, the biological role of NCAPD3 in the pathogenesis of breast cancer has not been elucidated. Evidence suggests that targeting ferroptosis can inhibit the progression of breast cancer. Moreover, 2,3,5,4’-Tetrahydroxystilbene-2-O-β-D-glucoside (THSG) could modulate MCF-7 cell proliferation in our previous study. Therefore, we aimed to investigate the potential mechanism by which NCAPD3 mediates ferroptosis in THSG inhibition of T47D cell proliferation by full-length transcriptome sequencing.MethodsAlternative splicing analysis was performed based on full-length transcriptome sequencing and the overlapping genes in differentially expressed transcripts (DETs) and differential alternative splicing (diAS) were obtained. Further, RT-PCR was used to validate the type of alternative splicing. And the hub genes (transcripts) were selected using the bioinformatics analysis, quantitative polymerase chain reaction (qPCR) and Western blotting (WB). Moreover, cell cycle and ferroptosis were assessed using flow cytometry analysis and WB respectively. Mechanically, cell viability and clone formation was detected using Biochemical kit. And siRNA of Ncapd3 was transfected into T47D cells to detect the expression levels of ferroptosis-related proteins (WB) and cell viability (MTT).Results40 overlapping transcripts of DETs and diAS were obtained consistent with the analysis of full-length transcriptome sequencing, and Ncapd3 (Ncapd3-203) is key gene (transcript), which was also highly expressed in breast cancer and THSG could inhibit the mRNA and protein expression. Moreover, THSG could induce cell cycle arrest in G2/M stage and reduce ferroptosis-related protein expression (xCT and GPx4). Mechanically, we found that THSG inhibits the cell proliferation and clone formation in T47D cells, and Ncapd3 inhibition could inhibit (xCT and GPx4) proteins expression, which regulated THSG-suppressing effect in T47D cells.ConclusionTHSG could inhibit the proliferation in T47D cells by NCAPD3 -dependent ferroptosis, which provided novel insights into targeted strategy for breast cancer.